THE USE OF VIDEO YOUTUBE TO IMPROVE STUDENTS ENGLISH VOCABULARY AT SMK MITRA NUSANTARA KOTA BEKASI IN ACADEMIC 2023/2024 - TASYA ALVERINA; YON A. E; ISWANDINI AGUSTIN (Universitas Mahasaraswati K. Mataram, 2024)
English is a global language that serves as a link between different parts of the world. Rich vocabulary and mastery of sentence structure are two of the many important elements in learning English. This study aims to identify the effectiveness of using YouTube videos in improving students' vocabulary and learning motivation in learning English. The method used is Classroom Action Research (PTK) involving cycles of planning, action, observation, and reflection. The research subjects were 28 students of class XI of Light Vehicle Engineering at SMK Mitra Nusantara in the academic year 2023/2024. Data were collected through observation, interviews, and initial and final tests. Data analysis was carried out qualitatively and quantitatively. The results showed that there was an increase in students' active participation and an increase in vocabulary scores. The pre-test average score of 59.64 increased to 70.07 in the cycle 1 post-test, and to 80.39 in the cycle 2 post-test. The number of students who met the Minimum Completion Criteria (KKM) increased from 10 students in the pre-test, to 18 students in cycle 1, and 24 students in cycle 2. The findings indicate that the use of YouTube videos as learning media is more effective than conventional methods in improving students' English vocabulary. The researcher suggests that teachers consider the integration of audio-visual media such as YouTube videos in English language learning to improve students' learning outcomes.